PENGARUH TECHNOLOGY ACCEPTANCE MODEL (TAM) PADA KEMAMPUAN KEYAKINAN DIRI ATAS KOMPUTER PENGGUNA SISTEM INFORMASI AKUNTANSI DI PT BANK RAKYAT INDONESIA, TBK. CABANG GIANYAR - Putu Yudha Asteria Putri (JOURNAL OF APPLIED MANAGERIAL ACCOUNTING, 2019)
This study aims to determine the extent to which the Technology Acceptance Model (TAM) is used in the implementation of activities at PT Bank Rakyat Indonesia, Tbk. and its effect on self confidence in computers. Moreover PT. Bank Rakyat Indonesia (BRI), Tbk. is one of the state-owned banking companies, the assessment of employee satisfaction should be the focus of attention, both from management and the public who have bought shares or become a customer at the bank. This study took 124 research samples, namely the purposive sampling method with the criteria for employees who became the study sample were employees using the Accounting Information System. Multiple linear regression techniques are used in this study and get the results of the Technology Acceptance Model which consists of perceived easy of use, perceived usefulness and actual usage have a positive effect on self-confidence of the computer users of Accounting Information Systems at PT Bank Rakyat Indonesia, Tbk. Gianyar